The exemplary memory of the armed conflict as a condition of possibility in the particular singular and meaning categories - Mosquera Mosquera, Carlos Enrique; Bustamante Zamudio, Guillermo (Rastros Rostros, 2026)
This article, derived from the research “The formation of the subject from exemplary memory. A theoretical bet for the school”, aims to carry out a critical reflection to establish conditions of possibility in the formation of the subject, based on the knowledge of their past, the domain of symbolic perspective, and the production of meaning according to the education received. The chosen methodology was critical discourse analysis. The field diary and narrative were used as data collection instruments. In this process, the notion of exemplary memory proposed by Todorov was problematized, leading to the identification of the conditions under which exemplary memory can emerge in the student. The main conclusions are summarized as follows: 1) the subject’s singular reflection is a condition of possibility for the emergence of exemplary memory, provided that the subject is formed; 2) exemplary memory can arise in the subject from the particular and singular categories; and 3) exemplary memory becomes possible in the production of meaning constructed by the subject, according to their symbolic mastery and the education they have received.
Keywords: Condition of possibility; exemplary memory; sense; register; singular and particular